2022
DOI: 10.3389/fnagi.2022.945076
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulating roles of estrogen and phytoestrogens in cognitive therapeutics through epigenetic modifications during aging

Abstract: Estrogen (E2) plays important role in regulating hippocampal learning and memory. The decline of E2 after menopause affects learning and memory and increases the risk of neurodegenerative diseases like Alzheimer's disease (AD). Additionally, from the estrogen receptor (ER) mediated gene regulation; E2 also regulates gene expression at the transcriptional and posttranscriptional levels through epigenetic modifications. E2 recruits a number of proteins called co-regulators at the promoter region of genes. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…And also, a PET Study showed post-menopausal women showed significantly higher tau-PET signal in parieto-occipital regions, but were not moderated by Aβ burden or APOEε4 [ 87 ]. Additionally, following lower side effects compared with MHT, phytoestrogens as neuroprotective agents or epigenetic modifiers recover and maintain cognitive functions [ 88 , 89 ]. But, very little is known regarding the regulation of synaptic plasticity genes, and also the precise regulation mechanism needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…And also, a PET Study showed post-menopausal women showed significantly higher tau-PET signal in parieto-occipital regions, but were not moderated by Aβ burden or APOEε4 [ 87 ]. Additionally, following lower side effects compared with MHT, phytoestrogens as neuroprotective agents or epigenetic modifiers recover and maintain cognitive functions [ 88 , 89 ]. But, very little is known regarding the regulation of synaptic plasticity genes, and also the precise regulation mechanism needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…[ 62 ] Furthermore, lignans may play neuromodulatory actions as epigenetic modifiers and regulate gene expression through epigenetic modifications related to synaptic plasticity genes, learning and memory. [ 63 ] Phenolic acids are consumed through common foods, such as nuts, apple, coffee, and tea. Although data specifically on phenolic acid intake and cognitive outcomes are scarce, there is some evidence in the scientific literature that consumption of walnuts, [ 64 ] coffee, [ 65 ] and tea [ 66 ] was associated with lower odds of cognitive decline, despite no acute effects on established cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetics, the modification of DNA and DNA activity, can occur across the lifespan [115,116] and can occur during aging [117], often in response to environmental stressors [118]. Such changes can be reversible [16,109,119], and thus, such a system is dynamic and not unidirectional.…”
Section: Involvement Of Epigenetic Modification Across the Lifespan O...mentioning
confidence: 99%